Performance Measurement Through Balanced Scorecard Approach - Lukman Chalid; Darwis Lannai; Muhammad Syafi'i A. Basalamah (Jurnal Manajemen Bisnis, 2021)
The purpose of this research is to assess the performance of health centers using the Balanced Scorecard (BSC) framework from four perspectives: the customer perspective, the internal process perspective, the learning and growth perspective, and the financial perspective. The BSC application is intended to measure organizational performance from a variety of perspectives, not just financial ones; there must be a balance of financial and non-financial perspectives. This means that BSC is a strategic approach to evaluating an organization's performance that balances the interests of various stakeholders by balancing short- and long-term objectives.